Fat perception in the human frontal operculum, insular and somatosensory cortex - Thomas Wistehube (Nature Portfolio, 2018)
Abstract Here, we combined magnetic resonance imaging with lesion-symptom mapping in patients with chronic brain lesions to investigate brain representations of sugar and fat perception. Patients and healthy controls rated chocolate milkshakes that only differed in sugar or fat content. As compared to controls, patients showed an impaired fat, but not sugar perception. Impairments in fat perception overlapped with the anterior insula and frontal operculum, together assumed to underpin gustatory processing. We also identified the mid-dorsal insula as well as the primary and secondary somatosensory cortex - regions previously assumed to integrate oral-sensory inputs. These findings suggest that fat perception involves a specific set of brain regions that were previously reported to underpin gustatory processing and oral-sensory integration processes.